Prevalence of poultry diseases in Gazipur district of Bangladesh - Hassan, Md Kamrul; Kabir, Md Humayun; Abdullah-Al-Hasan, Md; Sultana, Shobnom; Khokon, Md Shohidul Islam; Kabir, S M Lutful (Asian Journal of Medical and Biological Research, 2016)
This study was designed with a view to investigate the prevalence of poultry diseases in Gazipur district of Bangladesh. A total of 679 poultry birds (313 layers, 338 broilers and 28 cockrels) either dead or live were brought for diagnosis of diseases at Gazipur Sadar Upazilla Veterinary Hospital. The diseases were diagnosed on the basis of history, clinical signs and post-mortem findings. The diseases encountered in layers were bacterial diseases 52.29% (salmonellosis 38.56%, colibacillosis 6.7%, fowl cholera 4.79% and necrotic enteritis 1.60%), viral diseases 23.95% (avian influenza 2.56%, Newcastle disease 16.61%, infectious bronchitis 3.19% and avian leucosis 0.64%), mycoplasmal disease (mycoplasmosis 14.70%) and protozoal disease (coccidiosis 5.75%). Salmonellosis was most prevalent disease in age group of >20 weeks, while Newcastle disease most common in 8 to 20 weeks of age group. In case of broiler, bacterial diseases 28.99% (salmonellosis 21.30% and colibacillosis 7.69%), viral diseases 53.24% (infectious bursal disease 28.99%, Newcastle disease 8.87% and infectious bronchitis 15.38%), mycoplasmal disease (mycoplasmosis 7.1%) and protozoal disease (coccidiosis 6.5%). In cockrels, the most prevalent disease was colibacillosis 35.71% followed by salmonellosis 28.57%, Newcastle disease 14.28% and mycoplasmosis14.28%. So among the diseases, salmonellosis is most prevalent disease followed by infectious bursal disease and mycoplasmosis in different kinds of poultry of Gazipur district of Bangladesh. Asian J. Med. Biol. Res. March 2016, 2(1): 107-112